2016
DOI: 10.1159/000445733
|View full text |Cite
|
Sign up to set email alerts
|

RASopathies: Presentation at the Genome, Interactome, and Phenome Levels

Abstract: Clinical symptoms often reflect molecular correlations between mutated proteins. Alignment between interactome and phenome levels reveals new disease genes and connections between previously unrelated diseases. Despite a great potential for novel discoveries, this approach is still rarely used in genomics. In the present study, we analyzed the data of 6 syndromes belonging to the RASopathy class of disorders (RASopathies) and presented them as a model to study associations between genome, interactome, and phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…These clinical entities, for example, comprise hypo-gonadotrophic hypogonadism (Kallmann syndrome—MIM: 308700), where MPS led to the identification of additional candidate genes [ 58 ]. Research progress has been made in the case of Klinefelter syndrome by application of testis transcriptomic analysis [ 59 ] MI is also commonly associated with rare syndromes with maldescended testes where most of the progress in research is again due to the application of MPS and bioinformatics: Noonan—MIM:163950 [ 60 ], Cleidocranial dysplasia—MIM:119600 [ 61 ], Bloom—MIM:210900 [ 62 ] and Silver–Russel syndromes—MIM:180860 [ 63 ]. Likewise, primary ciliary dyskinesia (MIM: 244400) and myotonic dystrophy 1 (MIM: 160900), which are associated in their milder forms with MI, have been subjected to similar research strategies [ 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…These clinical entities, for example, comprise hypo-gonadotrophic hypogonadism (Kallmann syndrome—MIM: 308700), where MPS led to the identification of additional candidate genes [ 58 ]. Research progress has been made in the case of Klinefelter syndrome by application of testis transcriptomic analysis [ 59 ] MI is also commonly associated with rare syndromes with maldescended testes where most of the progress in research is again due to the application of MPS and bioinformatics: Noonan—MIM:163950 [ 60 ], Cleidocranial dysplasia—MIM:119600 [ 61 ], Bloom—MIM:210900 [ 62 ] and Silver–Russel syndromes—MIM:180860 [ 63 ]. Likewise, primary ciliary dyskinesia (MIM: 244400) and myotonic dystrophy 1 (MIM: 160900), which are associated in their milder forms with MI, have been subjected to similar research strategies [ 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of protein-protein interactions was examined in a study by Cannistraci et al ( 17 ), where such interactions revealed the relation between co-presence of cardiomyopathy and cryptorchidism; two symptoms of the RASopathies. The study by Pevec et al ( 70 ) also provided a baseline for future studies of associations between interactome and phenome in RASopathies, additionally presenting data at genome, interactome, and phenome levels and as an integrated network of all three data types.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics can make sensitive genome annotations more accurate (Brosch et al., ), as well as confirm novel splice variants seen in RNA‐seq data (Gascoigne et al., ). Recently, an integrated bioinformatics approach was performed to understand the RASopathy class of disorders to identify protein–protein interaction in disease context by integrating genomic, phenomic, and interactome information from HGNC, OMIM, and GeneReviews (Pevec, Rozman, Gorsek, & Kunej, ). Deriving personalized, integrated databases for individual patients can be a robust strategy for clinical molecular diagnosis and therapy.…”
Section: Promise Of Functional Genomics and In Vivo In Vitro Validatmentioning
confidence: 99%